PENGARUH NON-PERFORMING FINANCING DAN FINANCING TO DEPOSIT RATIO TERHADAP RETURN ON ASSET PADA PERBANKAN SYARIAH INDONESIA 2020-2024 - Masalingi, Abdurrahman; Sopingi, Imam; Musfiroh, Anita; K, Kusnul Ciptanila Yuni (Diponegoro Journal of Islamic Economics and Business, 2025)
This study aims to analyze the influence of Non-Performing Financing (NPF) and Financing to Deposit Ratio (FDR) on Return on Assets (ROA) in Indonesian Islamic banks during the 2020-2024 period. A quantitative approach was employed using multiple linear regression analysis with secondary data from financial reports of Islamic banks registered with the Financial Services Authority (OJK). The findings reveal that NPF has a significant negative effect on ROA, while FDR does not show a significant influence. These results highlight the necessity of improving financing quality to support Islamic banks' profitability. This study offers insights for Islamic bank management in credit risk management and third-party fund efficiency, while contributing to Islamic finance literature in the post-pandemic era.